«In God I Know Who I Am». The Role of Christian Experience in Biographical Identity - Amo Usanos, Rafael; Giménez Rodríguez, Carlos (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2024)
The question of biographical identity has become one of the pivotal ideas of our time and has come to transform our own intimacy. It is logical to think that it also has its place in today’s Christian experience. After a description of its definition, elements and dynamisms, this work puts in parallel a double quest. On the one hand, it describes the place of this question in the Christian experience by looking for it in testimonies of young people or materials prepared for them. On the other hand, it searches for this question in the proposal of Pope Francis’ magisterium on holiness to the People of God and, especially, to young people. On these two paths, the work ends with a theological balance and a pastoral prospective in which the theological nuclei that must be deepened in order to offer an inculturated Christian thought in this cultural moment are brought to light.
Keywords: identity; holiness; inculturation; pope Francis; youth